(untitled) (Hungarian Journal of Industry and Chemistry, 2011)
The better understanding and optimization of fluid flow, injection, mixing and combustion processes in internal combustion engines are of critical importance in regard to compliance of the emission standards. Presented here is a complex simulation method, which provides transient fluid flow results in a cylinder of a gasoline engine. The model includes moving boundaries. Through the intake port and open intake valve, air is flown into the combustion chamber. Fuel is injected. In the compression stroke, after closing the intake valve, the mixing process is shown. At the top dead center (TDC) ignition is set, which results in combustion of the fuel-air mixture in the power stroke. In the exhaust stroke the burnt gases leave the combustion chamber through the open exhaust valve and the exhaust port. With the results of this simulation, it is possible to determine the temperature and heat transfer coefficients on the walls of the combustion chamber, and to define the thermal load. This load can later be used in a structural analysis of the parts of the combustion chamber, where heat transfer and expansion is calculated.